Optimization of a H-Darrieus turbine through parametric geometry based on Joukowsky transformation for low-TSR operational ranges - Baca Bernabe, Giusep Alexander (2024)
The depletion of traditional fossil fuel resources due to increased energy usage has led to efforts to promote renewable energy sources such as wind energy. This study aims to identify the optimal profile for an operational range (TSR = 2.33, 2.64, and 3.09) in terms of performance through the numerical integration of the Cp-TSR curve by combining Computational Fluid Dynamics (CFD) with the Metamodel of Optimal Prognosis (MOP) response surface approach. Three parameters (a/b ratio, m, and pitch angle) are analyzed using the Joukowsky transformation parametrization methodology for symmetrical airfoils. The optimized turbine, performed using Gradient-based approaches, achieved a higher average Cp at each TSR compared to the traditional NACA 0021. Furthermore, a comparative analysis of non-dimensional velocity and pressure contour between the optimal and the original profile was conducted. The study demonstrated that the approach used in coupling CFD modeling and optimization tools is reliable, cost-effective, and appropriate for fluid flow phenomena for high-dimensional and computationally expensive CFD models at different TSR.